Dyandi: A Political Fiction - Doyle, Timothy (Melbourne Books, 2014)
Dr Thomas McMahon, a self-assured and ambitious Australian environmentalist; journeys into the Philippines, intending to 'save' the tribal peoples of Mindanao and their mountain environment from the exploitation of Horizon Mining Corporation (HMC). Instead, the country changes him in ways that he never thought possible. Tom is in his mid-thirties, married, with a successful academic career and important international environmental connections. He heads The Melbourne Environment Centre which locks horns with the Company. This battle spills over into the Philippines, where HMC is launching a new mining operation after uncovering the largest copper deposit in Asia. Tom, a political pragmatist who campaigns on climate change and sustainable development, becomes enmeshed in a network of green militant insurgents who see him and his campaign as part of the problem. Tom discovers that people are the primary threatened species-not birds, pandas or whales.